Influence of nitrogen fertilization on the characteristics of potato starch - Ebúrneo, Juliana Marques [UNESP]; Garcia, Emerson Loli [UNESP]; dos Santos, Thaís Paes Rodrigues [UNESP]; de Souza, Emerson de Freitas Cordova [UNESP]; Soratto, Rogério Peres [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Leonel, Magali [UNESP] (Southern Cross Publishing, 2018)
This study evaluated the effect of nitrogen fertilization rates on the characteristics of potato starch. The experimental design was randomized block with four replications. The treatments were composed of four rates of N (0, 80, 120 and 160 kg ha-1). After 117 days of planting the harvested tubers were sanitized and the starch extracted. The starches of the different treatments were analyzed for the shape and distribution of size, X-ray pattern, crystallinity, amylose, minerals, pasting and thermal properties. Results showed that the fertilization did not cause alteration in the shape of the starch granules but the sizes of granules increased with the application of higher rates of nitrogen fertilizer. All potato starches had X-ray pattern B-type and crystallinity decreased when nitrogen fertilizer rates increased up to 120 kg ha-1. Fertilization did not interfere in content of amylose. Nitrogen rates promoted a decrease in the phosphorus, calcium and magnesium contents in the starches. The starches had their initial and peak temperatures of gelatinization decreased with increasing fertilizer rates, but there was no interference of this practice in the enthalpy. The highest peaks of viscosity and breakdown were observed in starch extracted from potatoes grown with the application of 80 kg ha-1 of Entec® 26 fertilizer. These results indicated important modifications in potato starch properties grown at different rates of nitrogen fertilization and can provide information for starch applications in the food and non-food industries.
Keywords: Minerals; Nitrogen; Solanun tuberosum; Starch; Thermal properties